2021
DOI: 10.1097/dcr.0000000000001863
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Allogeneic Adipose Tissue-Derived Mesenchymal Stem Cells for the Treatment of Complex Perianal Fistulas Not Associated With Crohn’s Disease: A Phase I Clinical Trial

Abstract: BACKGROUND: Anal fistula treatment aims to eradicate the fistula, preserve the sphincter, prevent recurrence, and allow an early return to daily activities for the patient. Because of the difficulty of achieving these goals, stem cell-based therapy has emerged for the treatment of complex perianal fistula with promising results. OBJECTIVE: The objective of this study was to evaluate the safety of allogeneic mesenchymal stem cells in the treatment of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Another recent study on fistula surgery with or without injection of ASCs in complex anal fistulas reported that the healing rate was 63.8% in the experimental group compared with 15.5% in the group treated with surgery alone ( p < 0.001), with a better postoperative course in terms of pain ( 30 ). A previous step with the seton drainage and closure of the internal opening seems to be the standardization in the technique, agreeing with a recent study in the literature ( 31 ). In recent metanalysis healing rate is similar (61,5%), in the group with cryptoglandular fistula treated with ASCs, but there is no a systematic description of complications ( 32 ).…”
Section: Results Of Ascs In Cryptoglandular Anal Fistulasupporting
confidence: 86%
See 1 more Smart Citation
“…Another recent study on fistula surgery with or without injection of ASCs in complex anal fistulas reported that the healing rate was 63.8% in the experimental group compared with 15.5% in the group treated with surgery alone ( p < 0.001), with a better postoperative course in terms of pain ( 30 ). A previous step with the seton drainage and closure of the internal opening seems to be the standardization in the technique, agreeing with a recent study in the literature ( 31 ). In recent metanalysis healing rate is similar (61,5%), in the group with cryptoglandular fistula treated with ASCs, but there is no a systematic description of complications ( 32 ).…”
Section: Results Of Ascs In Cryptoglandular Anal Fistulasupporting
confidence: 86%
“…The association with fibrin glue was constant in the first studies ( 26 , 27 ), rare the use of other procedures like anal plug ( 28 ). In last year it seems to be essential for the technique to associate the closure of the internal orifice of the fistula tract ( 20 , 22 , 30 , 31 ), with sometimes a previous application of a seton. It is not possible to evaluate the use of ASCs alone, without those described procedures, because considered as integral part of the technique.…”
Section: Results Of Ascs In Cryptoglandular Anal Fistulamentioning
confidence: 99%
“…However, more trials are needed before recommendations can be made regarding the use of MSCs for cryptoglandular fistulas. [263][264][265][266][267]…”
Section: Anorectal Fistula Associated With Crohn's Disease Ismentioning
confidence: 99%
“… 38 Further trials on autologous tissue implantation have been attempted for fistulas in patients with CD in phase 1 trials and RCTs. Autologous subcutaneous, 39 adipose‐derived, 40 and allogeneic mesenchymal stem cells, 41 as well as bone marrow‐derived mesenchymal stromal cells, 42 were harvested in these trials, and the results suggested that such treatments for fistulas may be effective and feasible (Table 3 ). In a meta‐analysis (n = 1252), the stem cell treatment group had a higher rate of fistula healing than the placebo group (61.8% vs 40.5%, OR: 2.21).…”
Section: Ibdmentioning
confidence: 99%